An Improved Resonant Controller for AMB-Rotor System Subject to Displacement Harmonic Disturbance - Li, Jinlei; Liu, Gang; Cui, Peiling; Zheng, Shiqiang; Chen, Xi; Chen, Qi (IEEE transactions on power electronics, 2022)
The controller contains harmonic components due to the detection error of the displacement sensor. The harmonic component acts on the magnetic bearing coil in the form of harmonic current, resulting in undesirable harmonic vibration force, which is not conducive to the microvibration control of active magnetic bearing (AMB) rotor system. In order to solve the problems of slow response speed and limited harmonic frequency range in series mode, an improved resonant controller in parallel mode is proposed in this article, which greatly improves the response speed of the system and the suppression effect at harmonic frequency. In addition, the gain and phase angle at each harmonic frequency can be adjusted, so the robustness of each harmonic frequency can be independently controlled, and the system stability can be guaranteed in a wide range of operating speeds. Finally, the effectiveness of the proposed algorithm is verified by simulation and experiment, which has important significance and application value for harmonic current suppression of AMB-rotor system.